Juglone and KPT6566 Suppress the Tumorigenic Potential of CD44+CD133+ Tumor-Initiating Caco-2 Cells In Vitro and In Vivo - Kim, Junghoon; Lee, Seonock; Sun, Ruijing; Kim, Jungho (Frontiers in Cell and Developmental Biology, 2022)
Pin1, a cis/trans isomerase of peptidyl-prolyl peptide bonds, plays a crucial role in the pathogenesis of many human cancers. Although chemical inhibitors of Pin1 show potent antitumor therapeutic properties against various cancers, their effect on colorectal cancer, especially colorectal tumor-initiating cells, remains unknown. Here, we investigated the effect of Juglone and KPT6566 on Caco-2 cells and tumor-initiating Caco-2 cells. Juglone and KPT6566 inhibited cell growth and colony formation, and induced apoptosis of Caco-2 cells. We also found that Juglone and KPT6566 downregulated expression of G1-phase-specific cyclins and cyclin-dependent kinases in a time-dependent manner, consistent with suppression of Caco-2 cell proliferation and colony formation. Although tumor-initiating cells are thought to be responsible for resistance to traditional chemotherapeutic drugs, our experiments demonstrate that Juglone or KPT6566 kill both tumor-initiating and non-tumor-initiating Caco-2 cells with equal or similar efficacy. Finally, when CD44+CD133+ tumor-initiating Caco-2 cells were injected into NSG mice, Juglone or KPT6566 led to a meaningful reduction in tumor volume and mass compared with tumors isolated from mice that received control treatment. Overall, these results indicate that chemical Pin1 inhibitors may be a valuable therapeutic option against colorectal tumor-initiating cancer cells.